Salvia lachnostachys Benth has antitumor and chemopreventive effects against solid Ehrlich carcinoma - Corso, Claudia Rita; Stipp, Maria Carolina; Adami, Eliana Rezende; da Silva, Luisa Mota; Mariott, Marihá; de Andrade, Sergio Faloni; de Souza Ramos, Edneia Amancio; Klassen, Giseli; Beltrame, Olair Carlos; Queiroz-Telles, José Ederaldo; de Oliveira, Cristhian Santos; Stefanello, Maria Élida Alves; et al. (Molecular Biology Reports, 2019)
Salvia lachnostachys is an herbaceous plant with anti-inflammatory, analgesic and cytotoxic properties. This study investigated the antitumor effect of an ethanolic extract of Salvia lachnostachys leaves (EES) in a solid Ehrlich carcinoma model. Ehrlich cells were inoculated subcutaneously in the right pelvic member (2 × 10 6 cells) in female Swiss mice. The animals were treated with vehicle (10 mL kg −1 , p.o.), EES (30 and 100 mg kg −1 , p.o.), or methotrexate (2.5 mg kg −1 , i.p.) for 21 days (early treatment) or 14 days (late treatment) after tumor inoculation, or 10 days before tumor inoculation and continued for 21 days after tumor inoculation (chemopreventive treatment). The acute toxicity test was performed according OECD guidelines Late treatment with EES had no antitumor effect. Early treatment with 100 mg kg −1 EES prevented tumor development, increased tumor necrosis factor-α (TNF-α) levels and decreased tumor superoxide dismutase (SOD) activity, interleukin-10 (IL-10) levels and Cyclin D1 expression, and tumor cell necrosis was observed. Chemopreventive treatment with EES for 10 and 31 days prevented tumor development in the same manner. EES treatment for 31 days decreased hepatic and tumor SOD activity, tumor IL-10 levels and Cyclin D1 expression, and increased tumor reduced glutathione, N -acetylglucosaminidase, reactive oxygen species, lipid peroxidation, TNF-α levels and Nrf2 expression. No toxicity was observed in the acute toxicity assay. In conclusion, EES had an antitumor effect by inhibiting Cyclin D1 expression and increasing inflammation with early and chemopreventive treatment. Modulation of the antioxidant system also contribute for the antitumor effects of EES.